Percepciones didácticas acerca de la investigación en el aula y el aprendizaje por problemas (2021)
Pedagogy as science or discipline of education is not apart from the worries and challenges that superior education considers at the moment, according to the intentions about quality processes and efficiency that are pronounced permanently. In this sense the university has directed its efforts to the reflection and study of the curriculum, the pedagogy and the didactics, as alternatives in the improvement of the teaching and learning process. Too many answers to the problem have been proposed, nevertheless traditional pedagogies continue anchored in the university scenes, in spite of the efforts of those who think about the academy and the education. It is for that reason that we see the necessity to present some didactic perceptions that would make possible an approach to classroom research and especially to the theory of learning by problems. In this sense some considerations under the title of “didactic perceptions” are proposed, so that the judicious examination of procedures and techniques used in the class classroom will permit the revision of the pedagogical task in the university. In the research context as pedagogical option some situations will be recreated which will lead to think deeply about educational acts that will improve the pedagogical moments in the classroom.